THE INFLUENCE OF FAMILY FUNCTIONING, MORAL DISENGANGEMENT ON RISK-TAKING BEHAVIOR AMONG METHAMPHETAMINE (ICE) ADDICTS (Contemporary Journal of Social Science Review, 2025)
The present study aimed to investigate the Influence of Family Functioning and Moral Disengagement on Risk-Taking Behavior in Methamphetamine (Ice) Addict. It was hypothesized that (1)- there will be a significant correlation between family functioning and moral disengagement and Risk-Taking Behavior in Methamphetamine (Ice) Addict. (2)- Higher levels of moral disengagement are positively associated with increased risk-taking behavior in methamphetamine addicts. 150 Ice addicts, aged 18 to 55 years (M=29.73, SD=9.02) selected from different clinics and rehabilitation centers of Lahore, Pakistan. Participants responded to demographic information form, The McMaster Family Functioning Scale (Epstein et al., 1983)), Moral Disengagement Scale (Bandura, 1996), and Risk-Taking Questionnaire de Haan et al. (2011). Results of Pearson’s product moment correlation showed that there is likely to be statistically significant relationship between moral disengagement and risk-taking behaviour. The study is significant in addressing the increasing concern of family functioning and moral disengagement and Risk-Taking Behavior in Methamphetamine (Ice) Addict. Future research should position family functioning as a transformative agent in disrupting the cognitive patterns that fuel moral disengagement and risk-taking in ice addicts. Emotionally connected and ethically grounded families can weaken the psychological justifications for harmful behaviors. Culturally sensitive, longitudinal studies are needed to explore how relational restructuring fosters long-term recovery